(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Savchenko L. Kompetentnosny concept of formation of the quality of future teachers. In article conceptual interpretation of a komptentnosny approach and specifics of its application are opened when teaching pedagogical disciplines in the highest to school. The Komptentnosny approach decides by professional basic knowledge and abilities, valuable orientations, motives of activity of the teacher, understanding of and world around, style of relationship on people, the general culture, ability to development of the creative potential.